Eukaryote microbes potential for bioflocs in the swamp aquaculture - Marini Wijayanti; Tanbiyaskur; Jubaedah, Dade; Saputra, Ade Bayu; Genti, Karta Sari; Agustina; Nabila Saraswati; Siti Yuliani; Hary Widjajanti (Indonesian Society of Scientific Aquaculture (ISSA), 2020)
ABSTRACT Eucaryote microbes have an important role in forming bioflocs in the brackishwater aquaculture ponds. Bioflocs become potential live feed for milkfish or crustacea. This study aimed to identify the potential of eukaryotic microbes in the brackishwater aquaculture as the biofloc candidates potential development. This study was done through the water quality assessment and potential indigenous microbes isolation approach. Sampling was retrieved from the water subcomposite and sediment on each intertidal inlet and outlet. The water quality of brackishwater pond and intertidal swamp tended to lack of nutrient as containing inoptimal dissolved oxygen, salinity, pH, and ammonia content for the milkfish culture. Therefore, liming and fertilizing should be done to enrich the indigenous microbes. Eucaryote microbe isolated from the enrichment media was the aquatic fungi (multicellular and unicellular fungi) and microalgae (bacillariophyta, chlorophyta, and cyanophyta). Fungi and yeast formed a floculation with microalgae. This form will become a biofloc candidate as a live feed and water quality controller for the development of brackishwater aquaculture in the swamp area. Keywords: eucaryote microbes, biofloc, aquaculture, pond, brackish water swamp ABSTRAK Mikrob eukariot berperan penting dalam pembentukan bioflok di tambak budidaya pada lahan rawa payau. Bioflok menjadi pakan alami untuk budidaya ikan bandeng atau udang. Tujuan riset ini adalah mengidentifikasi mikrob eukariot rawa payau potensial untuk pengembangan kandidat bioflok di akuakultur rawa payau. Riset ini dilakukan dengan pendekatan kualitas air serta isolasi mikrob indigenous tambak dan rawa pasang surut untuk mendapatkan isolat mikrob potensial sebagai kandidat pembentuk bioflok. Sampling dilakukan secara subkomposit pada air dan sedimen di setiap inlet dan outlet pasang surut. Kualitas air tambak dan rawa pasang surut menunjukkan kondisi oksigen terlarut, salinitas, pH, dan amonia berada di luar batas optimum budidaya ikan bandeng, sehingga perlu dilakukan pengapuran dan pemupukan untuk memperbanyak mikrob indigenous-nya. Isolasi mikrob eukariot dari media pengayaan diperoleh jenis fungi akuatik yang multiseluler dan uniseluler, sedangkan mikroalga yang diperoleh yaitu dari golongan Bacillariophyta, Chlorophyta, dan Cyanophyta. Fungi yang dapat membentuk hifa dapat merangkai mikroalga dan khamir untuk membentuk flok. Susunan ini diharapkan dapat menjadi bahan bioflok yang berguna sebagai pengendali kualitas air sekaligus pakan alami bagi pengembangan budidaya di lahan rawa payau. Kata kunci: mikrob eukariot, bioflok, budidaya, tambak, rawa payau